Newton's Law of Universal Gravity

Written by Jerry Ratzlaff on . Posted in Classical Mechanics

Newton's Law of Universal Gravitation

All objects in the universe exert a gravitational force of attraction on each other.

Newton's Law of Universal Gravitation formula

\( gravitational \; force   \;=\;    universal \; gravitational \; constant  \;   \frac { mass_1  \;\;x\;\;   mass_2  } {  distance^2 } \)

\(F_g = G \frac {m_1 m_2} {d^2} \)

Where:

\(F_g \) = gravitational force

\(G\) = universal gravitational constant  

\(m_1\) = mass of object 1

\(m_2\) = mass of object 2

\(d\) = distance between objects

Solve for:

\(m_1 = \frac {F_g   d^2} {G m_2} \)

\(m_2 = \frac {F_g   d^2} {G m_1} \)

\(d = \sqrt { \frac {G m_1 m_2} {F_g} } \)

 

Tags: Equations for Gravity